Paleo-Ice Stream Behavior: Retreat Scenarios and Changing Controls in the Ross Sea, Antarctica - Halberstadt, Anna Ruth Weston (2016)
Studying the history of ice-sheet behavior in Antarctica’s largest drainage basin, the Ross Sea, can improve understanding of patterns, timing, and controls on marine-based ice-sheet dynamics, and provide constraints on numerical ice-sheet models. Newly collected high-resolution multibeam swath bathymetry data, combined with two decades of legacy multibeam and seismic data, are used to map glacial landforms and reconstruct paleodrainage. Last Glacial Maximum grounded ice reached the continental shelf edge in the eastern but not western Ross Sea. Recessional geomorphic features in the western Ross Sea indicate virtually continuous retreat of the ice sheet in contact with the bed. In the eastern Ross Sea, well-preserved linear features and a lack of small-scale recessional landforms record rapid lift-off of grounded ice from the bed. Physiography exerted a first-order control on ice behavior, while seafloor geology played an important subsidiary role. This new analysis of retreat patterns suggests that: (1) a large embayment formed in the eastern Ross Sea; (2) retreat was complex and asynchronous between troughs; and (3) the eastern Ross Sea largely deglaciated prior to the western Ross Sea. Previously published grounding-line retreat scenarios are based on terrestrial observations; however, this work uses Ross Sea-wide geomorphology to constrain marine deglaciation.